Tell es-Samak (Šiqmōnā/Porphyréon) during the Persian Period Results of the Renewed 2010 – 2012 Excavations - Bar, Shay; Gekht, Yuli; Shamir, Nofar; Shalev, Yiftah 19XX- (2024)
Tell es-Samak ([Tel] Šiqmōnā/Πορφυρέον [south]), is one of the first southern Levantine coastal sites in which Persian period remains were found and properly published. The site was excavated by ELGAVISH in the 1970s. He describes two settlement layers from this period: a well-organized settlement (Stratum P) with two perpendicular streets between insulae, and a layer containing remains of a structure interpreted as a fortress above it. He dated the former to a short period during the first half of the 5th cent. B.C.E., and the latter to the end of the 4th cent. B.C.E. In renewed excavations in 2010-2012 remains of two rooms dating to the Persian period were exposed, probably part of a domestic structure, built directly above an earlier Iron Age stratum. They form part of ELGAVISH's Persian Stratum P, continuing it to the north. The revised plan of the structure resembles those published by ELGAVISH. Four sub-phases were exposed in this structure, consisting of raising floor levels and small inner renovations, implying that the settlement was not as short-lived as ELGA VISH suggested. No remains of the Late Persian stratum were found, and it seems that this layer was not as extended as the previous one, and did not cover the entire tell. Material culture remains, especially the pottery vessels, were identical to those found in all other Persian period southern Levantine coastal sites, and clearly belonged to the Phoenician xorve. We also present an intact 5th cent. B.C.E. Achaemenid bulla discovered at the site.
Keywords: Persian Period; Carmel Coast; Phoenicia; Levantine archaeology; Persische Zeit <550 bis 330 v. Chr.>